Implications of Critical Thinking, Creativity and Information Technology on Education - Adeleye, Joseph Olusola (NIU Journal of Social Sciences, 2018)
One can say that it is expedient in this present world that individual should strive towards the acquisition of at least basic knowledge of science and technology for proper development, most especially in the area of Education (teaching and learning). This is necessary to assess reasons properly as well as to possess tendency to ask probing questions and bind these with critical thought to serve as the basis of creative thinking.  This is because in todayâ€™s highly technological society, the critical demand for inventive scientists and technologists has highlighted the need for some means of identifying those individuals with the greatest creative promises.  In education where creative qualities appear to have formerly neglected in both teaching and testing, it is desirable to assess each individualâ€™s creative potential through critical thinking.  The assessment is important to pave way for the creative thinking that will lead to problem solving activity.  It is on this note that the paper focuses on the Implications of Critical thinking and Creativity on Information Technology in Education. Keywords:   Education, Creativity, Critical thinking and Information Technology